Targeted Genomic Disruption of H-ras and N-ras, Individually or in Combination, Reveals the Dispensability of Both Loci for Mouse Growth and Development - Esteban, Luis M. (American Society for Microbiology, 2001)
Mammalian cells harbor three highly homologous and widely expressed members of the ras family (H-ras, N-ras, and K-ras), but it remains unclear whether they play specific or overlapping cellular roles. To gain insight into such functional roles, here we generated and analyzed H-ras null mutant mice, which were then also bred with N-ras knockout animals to ascertain the viability and properties of potential double null mutations in both loci. Mating among heterozygous H-ras(+/−) mice produced H-ras(−/−) offspring with a normal Mendelian pattern of inheritance, indicating that the loss of H-ras did not interfere with embryonic and fetal viability in the uterus. Homozygous mutant H-ras(−/−) mice reached sexual maturity at the same age as their littermates, and both males and females were fertile. Characterization of lymphocyte subsets in the spleen and thymus showed no significant differences between wild-type and H-ras(−/−) mice. Analysis of neuronal markers in the brains of knockout and wild-type H-ras mice showed that disruption of this locus did not impair or alter neuronal development. Breeding between our H-ras mutant animals and previously available N-ras null mutants gave rise to viable double knockout (H-ras(−/−)/N-ras(−/−)) offspring expressing only K-ras genes which grew normally, were fertile, and did not show any obvious phenotype. Interestingly, however, lower-than-expected numbers of adult, double knockout animals were consistently obtained in Mendelian crosses between heterozygous N-ras/H-ras mice. Our results indicate that, as for N-ras, H-ras gene function is dispensable for normal mouse development, growth, fertility, and neuronal development. Additionally, of the three ras genes, K-ras appears to be not only essential but also sufficient for normal mouse development.